1988
DOI: 10.1095/biolreprod39.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Differences in the Stability of Mammalian Sperm Nuclei Assessed in Vivo by Sperm Microinjection and in Vitro by Flow Cytometry1

Abstract: To assess the structural stability of mammalian sperm nuclei and make interspecies comparisons, we microinjected sperm nuclei from six different species into hamster oocytes and monitored the occurrence of sperm nuclear decondensation and male pronucleus formation. The time course of sperm decondensation varied considerably by species: human and mouse sperm nuclei decondensed within 15 to 30 min of injection, and chinchilla and hamster sperm nuclei did so within 45 to 60 min, but bull and rat sperm nuclei rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(109 citation statements)
references
References 29 publications
8
101
0
Order By: Relevance
“…These experiments also show that the off-rate determined for hamster protamine 2 is not significantly different from that observed for protamine 1. This indicates that the previously reported finding that sperm containing substantial amounts of protamine 2 decondenses more rapidly in the oocyte after fertilization (42) must not be caused by differences in the affinities of the two protamines for DNA.…”
Section: Dna Condensation Induced By Protamines P1 and P2-insupporting
confidence: 70%
“…These experiments also show that the off-rate determined for hamster protamine 2 is not significantly different from that observed for protamine 1. This indicates that the previously reported finding that sperm containing substantial amounts of protamine 2 decondenses more rapidly in the oocyte after fertilization (42) must not be caused by differences in the affinities of the two protamines for DNA.…”
Section: Dna Condensation Induced By Protamines P1 and P2-insupporting
confidence: 70%
“…For this reason TRIS, which is a buffer solution maintaining stable (slightly alkaline) pH was used, • the detergent disodium tetraborate, which dissolves lipids. Differences within series and between animals or species may result from the number of disulfide bonds in the sperm nucleus [9,13]. Bull spermatozoa are condensed more easily than stallion spermatozoa because bull sperm nuclei are characterized by a higher concentration of disulfide bonds compared to human or mouse sperm nuclei and therefore they seem more resistant to the action of chemical preparations [9].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione is the major intercellular free thiol in mammalian oocytes. It plays a major role in reducing disulfide bonds between protamine, which contributes to subsequent dispersion of sperm chromatin during fertilization [13]. The use of GSH combined with heparin produced the expected result of decondensation of bull sperm nucleus [12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, human spermatozoa express both protamine 1 and protamine 2 (whereas rats have only protamine 1). It has been shown that the chromatin of spermatozoa from species expressing both protamines is more susceptible to decondensation (71); this property might also make it more susceptible to damage associated with oxidant exposure.…”
Section: Zubkova Effect Of Age On Spermatozoal Chromatin Fertil Stementioning
confidence: 99%